Mapping of the immunodominant T cell epitopes of the protein topoisomerase I. Issue 8 (12th July 2004) - Veeraraghavan, S; Renzoni, E A; Jeal, H; Jones, M; Hammer, J; Wells, A U; Black, C M; Welsh, K I; du Bois, R M
Abstract : Objectives: To identify the immunodominant T cell epitopes of the topoisomerase I protein in patients with systemic sclerosis (SSc) and control subjects, using computational analysis software (TEPITOPE) and T cell proliferation assays. Methods: Six oligopeptides, predicted by TEPITOPE software as potential topoisomerase protein epitopes, were used to perform T cell proliferation assays in 21 patients with SSc and 15 healthy controls. Results: A positive response to at least one of the peptides was seen in 10/21 patients and 7/15 healthy controls. Among responders, the proliferative response was limited to a single peptide in 6/7 healthy controls, whereas 5/10 patients responded to more than one peptide. In responding patients a significant correlation was found between disease duration and number of peptides inducing a response (p = 0.007). Conclusions: Several T cell epitopes of the topoisomerase I protein have been identified and evidence has been found to suggest epitope spreading in patients with SSc.